Can microbial communities regenerate? uniting ecology and evolutionary biology - Inkpen, S. Andrew (Convening science., 2022)
"You take antibiotics to fight an infection. Unfortunately, the treatment also kills the community of bacteria in your gut microbiome; you now have digestion issues. You might start eating yogurt to reintroduce good bacteria. Or, if the bacterial community is more significantly disordered, you might need a "fecal microbiota transplant" - a doctor transfers stool from a healthy donor into your gut. The new bacteria community thrives, and you can again digest your food. If all the same types of bacteria are present in this new community, has your microbiome "regenerated"? What if the bacteria are completely different, but they perform the same function? How do the answers to these questions change if we look at the cells in a regrown salamander limb or the flora in a replanted forest? In this second book in the Regeneration Series, a philosopher of science and molecular biologist, S. Andrew Inkpen and W. Ford Dolittle, investigate these questions and their consequences. As the examples above show, asking about whether microbial communities can regenerate, what that might mean, and why it matters is not just an academic question. Offering provocations and an understanding that go beyond the descriptive work that has been published to date, this book offers an accessible conceptual and theoretical understanding of regeneration and evolution in microbial communities that will be useful across disciplines including in philosophy of biology, conservation biology, microbiomics, evolutionary biology, and community ecology"--